Mechanical properties of laser powder directed energy deposited NASA HR-1 superalloy: Effects of powder reuse and part orientation. (April 2023) - Soltani-Tehrani, Arash; Chen, Poshou; Katsarelis, Colton; Gradl, Paul; Shao, Shuai; Shamsaei, Nima
Abstract: The feasibility of NASA HR-1 powder reuse for laser powder directed energy deposition (LP-DED) of thin-walled structures in the as-built surface condition was investigated in this study. Although continuously reusing the powder five times slightly reduced the number of fine particles in the powder and increased the mean particle size, changes in powder rheological properties were negligible. The similarities in powder flow between all reused conditions resulted in no variation in surface roughness, defects' size and spatial distributions, and microstructure of the as-deposited parts and, thus no differences on tensile and fatigue properties. The effects of different specimen orientations, loading direction being perpendicular or parallel to the building direction, on mechanical properties were also investigated. While no change in tensile strength was noted, tensile ductility was lower for the parallel specimens because of surface micro-notches being perpendicular to the loading direction, which led to an early onset of fracture. Due to accelerated crack initiation from these micro-notches, parallel specimens were also less resistant to fatigue failures. The fatigue failures always initiated from the specimen surfaces, and all specimens experienced a ductile fatigue crack growth mechanism characterized by clear striations on the fracture surface. Graphical abstract: Highlights: Powder reuse effects on LP-DED NASA HR-1 mechanical properties were investigated. Effects of specimen orientation with respect to building direction were studied. Five times reusing the powder did not affect the powder flowability. Powder reuse did not change microstructures, and tensile and fatigue properties. Specimens perpendicular to building direction showed better mechanical properties.